THE FAIR VALUE OF AUTHENTIC AND TRUE METHOD OF ASSESSING THE LIABILITIES OF THE COMPANY - S. Travinska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2013)
The article explores the nature of the category “assessment” in the scientific literature and normative documents; considered the types of assessments in the domestic and international practice; the methodology to assess the fair value of liabilities in accordance with IFRS; recommended methods for assessment of certain types of current liabilities accounting. Also the author describes the case for the use of different systems assessments of reflection of economic operations of the company. Defined the essence and necessity of application of the fair value in respect of the liabilities that would provide a true assessment of the financial condition of the enterprise and rational management accounting.